2020
DOI: 10.3390/cancers12103002
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometry as a Highly Sensitive Method for Specific Circulating Tumor DNA Analysis in NSCLC: A Comparison Study

Abstract: Plasma-based tumor mutational profiling is arising as a reliable approach to detect primary and therapy-induced resistance mutations required for accurate treatment decision making. Here, we compared the FDA-approved Cobas® EGFR Mutation Test v2 with the UltraSEEK™ Lung Panel on the MassARRAY® System on detection of EGFR mutations, accompanied with preanalytical sample assessment using the novel Liquid IQ® Panel. 137 cancer patient-derived cell-free plasma samples were analyzed with the Cobas® and UltraSEEK™ t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 31 publications
0
24
0
1
Order By: Relevance
“…Plasmonic nanoparticles are used in surface-enhanced Raman scattering (SERS) nanosensors for signal-amplification and mutations are identified based on specific Raman spectroscopy [47,48]. For matrixassisted laser desorption/ ionization time of flight mass spectrometry (MALDI-TOF-MS), biotin-labeled extended products are captured and eluted, then dispensed onto bioarrays for spectrum profiles [49]. Relatively, the electrochemical biosensors are more widespread and easier to fabricate, time-and cost-effective, rapidly responsive, and portable.…”
Section: Analytic Approachesmentioning
confidence: 99%
“…Plasmonic nanoparticles are used in surface-enhanced Raman scattering (SERS) nanosensors for signal-amplification and mutations are identified based on specific Raman spectroscopy [47,48]. For matrixassisted laser desorption/ ionization time of flight mass spectrometry (MALDI-TOF-MS), biotin-labeled extended products are captured and eluted, then dispensed onto bioarrays for spectrum profiles [49]. Relatively, the electrochemical biosensors are more widespread and easier to fabricate, time-and cost-effective, rapidly responsive, and portable.…”
Section: Analytic Approachesmentioning
confidence: 99%
“…Recent work by Lamy et al, 2020 have demonstrated the parallel use of the Cobas® EGFR mutation test. The study highlighted a 86% concordance between the UltraSEEK lung and Cobas® assays with similar sensitivity in EGFR mutation detected, in particular when cfDNA input was similar [20]. Another study performed in melanoma, using the UltraSEEK melanoma panel and digital droplet PCR for the detection of BRAF V600E showed that the UltraSEEK assay was as sensitive as digital droplet PCR [23].…”
Section: Discussionmentioning
confidence: 74%
“…However, the Qubit was found to detect higher concentrations of cfDNA compared to the Liquid IQ™. Studies have shown strong correlations between the two assays [20].…”
Section: Resultsmentioning
confidence: 99%
“…The use of a 68 mutations panel on cfDNA from melanoma patients showed the same sensitivity as ddPCR [ 63 ]. In NSCLC, the limit of detection of the UltraSEEK Lung Panel, consists of 73 variants, was 0.125–1% with low input of specific tumoral cfDNA fragments beforehand measured with the LiquidIQ Panel [ 64 ]. Of note, this study showed the importance of preanalytical cfDNA quality control and input amount for the accuracy of liquid biopsy testing.…”
Section: Detection Of Ctdna By Sequencing Technologiesmentioning
confidence: 99%